Comparison of progress curve analysis and initial rate kinetics for the estimation of identifiable enzyme kinetic parameters : a case study using two glycolytic enzymes from Sulfolobus solfataricus - Louw, Carla (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.